Effects of partial or complete laser-assisted hatching on the hatching of mouse blastocysts and their cell numbers - Chanchai Chailert (2018)
Background: It is still debatable whether a full-thickness assisted hatching (AH) is better than the partial zona thinning. In this research, we used a mouse model to study the effect of partial and complete laser-AH on the rate of completely hatched blastocyst and their cell numbers.Methods: In experiment 1, mouse morulae had 0, 1, 2 or 3 full-thickness openings of 10 microns created in the zona pellucida with an infrared laser beam. In the second experiment, 0, 1 and 2 openings of 20 microns were studied. In the third experiment, a full-thickness opening of 20 microns or quarter-thinning of the zonal circumference to a depth of 90% was compared with non-AH controls.Results: No difference in blastocyst formation was found in laser-treated groups and in the controls. In experiment 1, the rate of completely hatched blastocysts was significantly lower than the controls. In experiment 2 when the size of the opening was increased, blastocysts completely hatched at a significantly higher rate than that in the controls. In experiment 3, the rate of completely hatched blastocysts was the highest in the full-thickness group. Cell numbers in completely hatched blastocysts from both AH groups were significantly fewer than those in the controls.Conclusions: Full-thickness opening resulted in a higher rate of completely hatched blastocysts than quarter zonal-thinning and controls, but the cell numbers were significantly decreased. © 2013 Chailert et al.; licensee BioMed Central Ltd.